2019
DOI: 10.1111/ijac.13349
|View full text |Cite
|
Sign up to set email alerts
|

Theory and practice of rapid and safe thermal debinding in ceramic injection molding

Abstract: In this paper, the dynamic process of thermal debinding was analyzed. The critical thickness of debinding was defined as the thickness at which the steps to control dynamics change from diffusion of gas products in liquid binder to diffusion or permeation in pores. Subsequently, the equation of critical thickness was deduced. The results show that the critical thickness of debinding is independent of the thickness of the green body, but mainly depends on the particle size, solid content, and binder composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In both cases, two decomposition ramps can be observed, a ramp at low temperatures with a pronounced mass loss, and a ramp at higher temperatures with a lower mass loss rate. Each ramp corresponds to the progressive degradation of the polymers in the multicomponent binder system, as has been already observed for zirconia feedstocks for ceramic injection molding [ 50 ]. From Figure 5 , it can be seen that the slope of all the ramps is more pronounced and the degradation starts at lower temperatures for the feedstock than for the binder.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, two decomposition ramps can be observed, a ramp at low temperatures with a pronounced mass loss, and a ramp at higher temperatures with a lower mass loss rate. Each ramp corresponds to the progressive degradation of the polymers in the multicomponent binder system, as has been already observed for zirconia feedstocks for ceramic injection molding [ 50 ]. From Figure 5 , it can be seen that the slope of all the ramps is more pronounced and the degradation starts at lower temperatures for the feedstock than for the binder.…”
Section: Resultsmentioning
confidence: 99%
“…The TGA results confirmed that the chemical nature of the powder could change the kinetic of binder decomposition. Xie et al [30] used TGA coupled with FTIR spectrometry (TG-FTIR analysis) to quantitatively study and design the thermal debinding cycle for HPIM zirconia-based feedstocks and evaluate the effect of binder composition, decomposition rate, degradation temperature range, and products on the quality of debound parts. W.-K. You et al [31] used the TGA approach to design a thermal wick debinding cycle adapted to spherical iron-based feedstocks (i.e., to blends of micrometric and nanometric powders).…”
Section: Introductionmentioning
confidence: 99%